UPAYA PENCEGAHAN ANEMIA PADA REMAJA MELALUI PEMBERIAN TABLET FE DAN VITAMIN C DI SMK BAITUL HIKMAH - handayani, yuni; Handayani, Ririn; Puspita Sari, Melati; Anggraeni, Ernawati (LPPM Universitas dr. Soebandi, 2023)
Anemia is a condition where the hemoglobin and erythrocyte levels are lower than normal. Hemoglobin is less sensitive to the early stages of iron deficiency, but is useful for determining the severity of anemia. Adolescents have special nutritional needs, because at that time there is rapid growth and changes in physiological maturity occur due to the onset of puberty. Adolescent experience menstruation every month, where iron loss is ± 1.3 mg per day, so that the need for iron is greater than male adolescents. So it is necessary to provide education and understanding of Fe and Vitamin C tablets to prevent anemia. Reproductive readiness is obtained through education, administration of Fe and Vitamin C tablets to prevent anemia in adolescents. As for its activities through the provision of education which is the first step that refers to biomedical, behavioral and social prevention interventions that can increase the chances of having a healthy baby. objective : To be able to create reproductive health in Adolescent can be done through screening to prevent anemia. Screening is very useful and has a positive effect on maternal and child health and prevents maternal and child deaths starting during Adolescent. The purpose of this activity is to provide information, education and administration of Fe and vitamin C as an effort to prevent anemia in Adolescent and then monitor the accuracy of consuming Fe and vitamin C tablets. Metode: Activities to prevent anemia in adolescents will be carried out at SMK Baitul Hikmah, Jember Regency. Resulit: Adolescent were very enthusiastic and active in receiving the material and were able to apply the suggestions to take fe and vitamin c tablets according to schedule